New Insights for Febrile Urinary Tract Infection (Acute Pyelonephritis) in Children - Kyung-Yil Lee (Korean Society of Pediatric Nephrology, 2016)
Although asymptomatic bacteriuria, cystitis, and acute pyelonephritis (APN) have been categorized as urinary tract infections (UTIs), the immunopathogenesis of each disease is different. APN shows an age predilection; the majority of children (over 70-80%) with APN are under 1-2 years of age, with a male predominance. After 1-2 years of age, female predominance has been reported. This finding suggests that the immature immune state of infancy may be associated with the pathogenesis of APN. Escherichia coli is the most common etiologic agent; other uropathogens associated with UTIs originate from the host and comprise normal flora that are continuously altered by environmental factors. Therefore, uropathogens may have characteristics different from those of extraneous bacterial pathogens. Although antibiotic-resistant uropathogens, including extended-spectrum beta-lactamase-producing strains, are increasing in Korea and worldwide, treatment failure is rare in immune-competent children. The immunopathogenesis of APN remains unknown. Intact bacteria may not be the causative substances in renal cell injury; rather, smaller substances produced during bacterial replication may be responsible for renal cell injury and scarring. Moreover, substances from host cells such as proinflammatory cytokines may be involved in renal cell injury. A dimercaptosuccinic acid scan is used to detect the site of bacterial replication in the renal parenchyma, and may be influenced by the size of the focus and the stage of APN. Traditional aggressive studies used to identify vesicoureteral reflux after the first episode of APN have been modified because of rare cases of chronic kidney disease in patients with recurrent UTI.